Effect of different drying conditions on volatile compounds of Canelo pepper (Drimys winteri) - Negri, Livia M.; Spontón, Emiliano A.; Salgado, Oscar; Sancho, Ana; Denoya, Gabriela I. (Journal of Phytology, 2020)
Canelo pepper is produced with the fruit of Drimys winteri (Winteraceae family). Driven by gourmet cuisine, this product is becoming increasingly in demand. The aim of this work was to study the effect of two drying conditions on the composition of the volatile compounds of Canelo pepper from Ushuaia forests (Argentina). Two treatments were evaluated. A mild drying (in a ventilated dryer, 2 days at 30 °C) that produced green pepper (G) and a strong drying (on an unventilated stove 6 days at 43 °C), which produced brown pepper (B). Untreated samples were used as fresh control (F). The profile of the volatile compounds of Canelo pepper varied when the fruits were dried and also changed with the drying conditions. Besides, the milder treatment affected the volatile compounds from the pepper to a lesser extent than the stronger drying.